A g-C3N4 / Cu-MOF visible light catalytic nanocomposite material and its preparation method and application

By loading g-C3N4 on Cu-MOF material, the g-C3N4/Cu-MOF visible light catalytic nanocomposite was formed, which solved the problem of poor structural stability and weak visible light absorption capacity in algae photocatalytic inactivation, and effectively inhibited the growth of microcysticus and efficient degradation of microcysticus toxins.

CN116273182BActive Publication Date: 2025-04-29JIANGNAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310088619.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-02
Publication Date
2025-04-29
Estimated Expiration
2043-02-02

AI Technical Summary

Technical Problem

The existing copper-based metal organic framework compound (Cu-MOF) has poor structural stability, weak visible light absorption capacity, and low electron-hole pair separation efficiency in algae photocatalytic inactivation, which limits its photocatalytic performance.

Method used

By loading graphite-like carbon nitride (g-C3N4) on Cu-MOF material, a g-C3N4/Cu-MOF visible light catalytic nanocomposite is formed, which improves the separation efficiency of electron-hole pairs, reduces the optical band gap value, and enhances the visible light absorption performance.

Benefits of technology

The inhibitory efficiency of composite materials on microcysticus growth and the degradation efficiency of microcysticus toxin (MC-LR) are significantly improved, and the water stability and photocatalytic performance of Cu-MOF are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116273182B_ABST
    Figure CN116273182B_ABST
Patent Text Reader

Abstract

The present invention discloses a g-C3N4 / Cu-MOF visible-light catalytic nanocomposite and its preparation method and application, belonging to the technical field of algicides. The preparation of the g-C3N4 / Cu-MOF visible-light catalytic nanocomposite of the present invention is to load g-C3N4 on the Cu-MOF material to form a g-C3N4 / Cu-MOF visible-light catalytic nanocomposite. This material can improve the separation efficiency of electron-hole pairs of the Cu-MOF material, reduce the optical band gap value, water stability and visible-light absorption performance of the material, thereby improving the inhibition efficiency of the composite material on the growth of Microcystis aeruginosa and the degradation efficiency of microcystin (MC-LR); it has broad application prospects as an algicide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a g-C3N4 / Cu-MOF visible light catalytic nanocomposite material and a preparation method and application thereof, belonging to the technical field of algaecides. Background Art

[0002] Traditional methods of inhibiting algae, such as physical, chemical, and biological methods, all have their limitations. For example, physical methods such as ultrasound, mechanical salvage, and membrane separation involve large engineering workloads, low treatment efficiency, and high costs; chemical methods such as adding flocculants and algaecides (such as CuSO4) are prone to secondary pollution of water bodies; biological methods inhibit algae growth by introducing beneficial microorganisms into water bodies, but the effect is less stable and lasts for a long time.

[0003] As an emerging method, semiconductor photocatalysis technology has the advantages of high efficiency, low cost and environmental sustainability, and has been widely studied in the fields of CO2 reduction, biological sterilization, antibiotic degradation, etc. Metal organic framework compounds (MOFs) have shown great advantages in this field. At present, copper-based metal organic framework compounds (Cu-MOF) have shown great potential in the photocatalytic inactivation of cyanobacterial blooms, but their shortcomings such as poor structural stability, weak visible light absorption capacity, and low electron-hole pair separation efficiency limit their own photocatalytic performance.

[0004] Therefore, it is necessary to improve its photocatalytic performance through appropriate modification and enhance the inactivation efficiency of cyanobacteria blooms. Graphite-like carbon nitride (g-C3N4) has attracted widespread attention due to its good physicochemical stability, good visible light response, and easy separation of electron-hole pairs, but its properties such as rapid electron-hole recombination also limit its photocatalytic efficiency. Summary of the invention

[0005] [Technical issues]

[0006] Existing copper-based metal-organic framework compounds (Cu-MOF) have shortcomings such as poor structural stability, weak visible light absorption ability, and low electron-hole pair separation efficiency in the photocatalytic inactivation of algae, which limit their own photocatalytic performance.

[0007] [Technical solution]

[0008] In order to solve the above technical problems, the present invention provides a g-C3N4 / Cu-MOF visible light catalytic nanocomposite material and a preparation method and application thereof. The g-C3N4 / Cu-MOF visible light catalytic nanocomposite material is formed by loading g-C3N4 on a Cu-MOF material. The g-C3N4 / Cu-MOF visible light catalytic nanocomposite material can improve the separation efficiency of electron-hole pairs of the Cu-MOF material, reduce the optical band gap value of the material, and effectively improve the visible light absorption performance of the material, thereby improving the inhibition efficiency of the composite material on the growth of Microcystis and the degradation efficiency of Microcystin (MC-LR); and it has broad application prospects as an algaecide.

[0009] The first object of the present invention is to provide a method for preparing a g-C3N4 / Cu-MOF visible light catalytic nanocomposite material, the method comprising the following steps:

[0010] The g-C3N4 powder is dispersed in a solvent, and then slowly dropped into a mixed solution of Cu(CH3COO)2·H2O and terephthalic acid, and the mixed solution is vigorously stirred and ultrasonically oscillated; thereafter, it is incubated at 100-120°C for 6-10 hours, and the precipitate is separated after centrifugation, washed, and dried to obtain; wherein, the mass proportion of g-C3N4 in the g-C3N4 / Cu-MOF visible light catalytic nanocomposite material is 5-25wt%.

[0011] In one embodiment, the solvent is a mixed solution of DMF and ethanol in a volume ratio of 4:1.

[0012] In one embodiment, the mass ratio of Cu(CH3COO)2·H2O to terephthalic acid is 2 to 5:1.

[0013] In one embodiment, the centrifugation condition is 8000-10000 rpm, 10-20 min.

[0014] In one embodiment, the washing is washing the precipitate with ethanol for 4 to 5 times.

[0015] In one embodiment, the drying temperature is 40-60°C.

[0016] In one embodiment, the mass percentage of g-C3N4 in the g-C3N4 / Cu-MOF visible light catalytic nanocomposite material is 10-20wt%, preferably 10wt%.

[0017] The second object of the present invention is to provide a g-C3N4 / Cu-MOF visible light catalytic nanocomposite material prepared by the above method.

[0018] The third object of the present invention is to provide an application of the above-mentioned g-C3N4 / Cu-MOF visible light catalytic nanocomposite material in treating harmful algal blooms.

[0019] The fourth object of the present invention is to provide a method for inhibiting the growth of Microcystis aeruginosa based on g-C3N4 / Cu-MOF visible light catalytic nanocomposite material, wherein the method comprises exposing the above-mentioned g-C3N4 / Cu-MOF visible light catalytic nanocomposite material to Microcystis aeruginosa.

[0020] The fifth object of the present invention is to provide a method for improving the degradation rate of microcystin, which comprises using the above-mentioned g-C3N4 / Cu-MOF visible light catalytic nanocomposite material to degrade microcystin.

[0021] The sixth object of the present invention is to provide a method for improving the water stability of Cu-MOF materials, the method comprising: dispersing g-C3N4 powder in an organic solvent, then slowly dripping it into a mixed solution of Cu(CH3COO)2·H2O and terephthalic acid, vigorously stirring the mixed solution and ultrasonically oscillating it; then culturing it at 100-120°C for 6-10h, separating the precipitate after centrifugation, washing and drying to obtain the obtained material; wherein the mass ratio of g-C3N4 in the g-C3N4 / Cu-MOF visible light catalytic nanocomposite material is 2-20wt%.

[0022] [Beneficial Effects]

[0023] (1) The present invention forms a g-C3N4 / Cu-MOF visible light catalytic nanocomposite material by loading g-C3N4 on the Cu-MOF material. The g-C3N4 / Cu-MOF visible light catalytic nanocomposite material effectively improves the separation efficiency of the electron-hole pairs of the Cu-MOF material, reduces the optical band gap value of the material, and significantly improves the visible light absorption performance of the material, thereby enabling the composite material to effectively inhibit the growth of Microcystis and promote the degradation of Microcystis toxin (MC-LR);

[0024] (2) When the mass proportion of g-C3N4 in the g-C3N4 / Cu-MOF visible light catalytic nanocomposite prepared by the present invention is 10wt%, the inactivation efficiency of Microcystis aeruginosa reaches the best, and the inhibition rate reaches 52.13%; it has a significant photodegradation efficiency for microcystin toxins; it can be used as a high-efficiency algaecide and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1TEM images, XRD spectra and FTIR spectra of the composite materials prepared in Examples 1 and 2 of the present invention and Comparative Example 1; wherein (A) TEM image of Cu-MOF; (B) TEM image of 2wt% g-C3N4 / Cu-MOF; (C) TEM image of 5wt% g-C3N4 / Cu-MOF; (D) TEM image of 10wt% g-C3N4 / Cu-MOF; (E) TEM image of 15wt% g-C3N4 / Cu-MOF; (F) TEM image of 20wt% g-C3N4 / Cu-MOF; (G) TEM image of g-C3N4, Cu-MOF, 2wt% g-C3N4 / Cu-MOF XRD patterns of %g-C3N4 / Cu-MOF, 5wt%g-C3N4 / Cu-MOF, 10wt%g-C3N4 / Cu-MOF, 15wt%g-C3N4 / Cu-MOF, 20wt%g-C3N4 / Cu-MOF; (H)g-C3N4, FTIR spectra of Cu-MOF, 2wt%g-C3N4 / Cu-MOF, 5wt%g-C3N4 / Cu-MOF, 10wt%g-C3N4 / Cu-MOF, 15wt%g-C3N4 / Cu-MOF, 20wt%g-C3N4 / Cu-MOF;

[0026] Figure 2 The data graph shows the photocatalytic inactivation efficiency of harmful algal bloom Microcystis aeruginosa after exposure to different composite materials for 6 hours;

[0027] Figure 3 Photocatalytic performance of different composite materials (g-C3N4, Cu-MOF, 2wt% g-C3N4 / Cu-MOF, 10wt% g-C3N4 / Cu-MOF, 20wt% g-C3N4 / Cu-MOF): (A) UV-vis DRS spectrum; (B) Tauc spectrum; (C) photoluminescence spectrum;

[0028] Figure 4 The efficiency data of photodegradation of microcystin (MC-LR) by different composite materials (10 mg / L Cu-MOF, 2 wt% g-C3N4 / Cu-MOF, 10 wt% g-C3N4 / Cu-MOF, 20 wt% g-C3N4 / Cu-MOF);

[0029] Figure 5 This is the water stability data of g-C3N4 / Cu-MOF composite material. DETAILED DESCRIPTION

[0030] The present invention is further described below in conjunction with specific embodiments.

[0031] The embodiments provided below are not intended to limit the scope of the present invention, and the steps described are not intended to limit the order of execution. Those skilled in the art can make obvious improvements to the present invention in combination with existing common knowledge, which also fall within the scope of protection required by the present invention.

[0032] 1. Determination of chlorophyll a content

[0033] Determined according to HJ 897-2017 standard;

[0034] 2. In the present invention, Microcystis aeruginosa was used as the test algae species, which was purchased from the freshwater algae species bank of the Institute of Hydrobiology, Chinese Academy of Sciences. This algae species is widely distributed in my country, mainly in lakes such as Taihu Lake and Poyang Lake. The algae species were preserved and cultured using 1 / 2BG11 (pH 7.0) culture medium, and the culture conditions were: light intensity of 6000 Lux, spectral range of visible light (>420 nm), 12h:12h (light: dark) cycle, and the temperature was set to 25±1°C using air conditioning. Microcystis aeruginosa cells were inoculated into 100 mL of 1 / 2BG11 culture medium, so that the initial algae density was 1.0×10 6 The algal cell suspension was shaken once every 12 h and cultured to the logarithmic growth phase before subsequent experiments.

[0035] Example 1

[0036] A method for preparing a g-C3N4 / Cu-MOF visible light catalytic nanocomposite material, the method comprising the following steps:

[0037] 105 mg of g-C3N4 powder was dispersed in 2.5 mL of DMF and ultrasonically vibrated for 8 h. Then, it was slowly dropped into 50 mL of a mixed solution containing 5 mmol Cu(CH3COO)2·H2O and 1.8 mmol C8H6O4. The mixed solution was vigorously stirred for 10 min and ultrasonically vibrated for 1 h. Then, it was incubated at 120°C for 9 h. After centrifugation (8000 rpm, 20 min), the precipitate was separated, washed four times with ethanol, and dried at 50°C to obtain a 10 wt% g-C3N4 / Cu-MOF nanocomposite material.

[0038] Example 2

[0039] The amounts of g-C3N4 in Example 1 were adjusted to 21 mg, 53 mg, 158 mg and 210 mg respectively, and the other conditions were the same as those in Example 1.

[0040] The prepared nanocomposites were 2wt% g-C3N4 / Cu-MOF, 5wt% g-C3N4 / Cu-MOF, 15wt% g-C3N4 / Cu-MOF and 20wt% g-C3N4 / Cu-MOF respectively.

[0041] Comparative Example 1

[0042] 5 mmol Cu(CH3COO)2·H2O and 1.8 mmol C8H6O4 (terephthalic acid) were dissolved in 50 mL solvent (the volume ratio of DMF and ethanol was 4:1) and ultrasonically shaken for 1 hour; then incubated at 120°C for 9 hours, the blue precipitate was separated by centrifugation (8000 rpm, 20 min), washed 4 times with ethanol, and the obtained solid product was dried at 50°C to obtain Cu-MOF.

[0043] Nanocomposite material characterization

[0044] 1. Transmission electron microscopy (TEM) XRD spectrum and FTIR spectrum were used to measure g-C3N4, Cu-MOF prepared in Comparative Example 1, 2wt% g-C3N4 / Cu-MOF, 5wt% g-C3N4 / Cu-MOF, 10wt%

[0045] The morphology and size of g-C3N4 / Cu-MOF, 15wt% g-C3N4 / Cu-MOF, and 20wt% g-C3N4 / Cu-MOF were characterized. Figure 1 As shown;

[0046] from Figure 1 It can be seen that both Cu-MOF and g-C3N4 / Cu-MOF nanocomposites have rod-like structures with a length of about 1 μm and a width of about 100 nm.

[0047] The XRD spectra show the characteristic peaks of g-C3N4 at 2θ=13°(100), 27.3°(002) and Cu-MOF and g-C3N4 / Cu-MOF nanocomposites at 2θ=9.4°(220), 13.8°(400), 15.2°(331), 18.1°(333), respectively. Figure 1 H).

[0048] FTIR spectra showed that g-C3N4 -1 、1250-1730cm -1 、3010-3384cm -1 and Cu-MOF and g-C3N4 / Cu-MOF nanocomposites at 680cm -1 ,1480cm -1and 1650cm -1 characteristic peaks.

[0049] Example 3

[0050] A method for inhibiting the growth of Microcystis aeruginosa based on g-C3N4 / Cu-MOF visible light catalytic nanocomposite material, the method comprising:

[0051] The cell suspension of Microcystis aeruginosa was exposed to the g-C3N4 / Cu-MOF visible light catalytic nanocomposites prepared in Example 1 and Example 2, respectively. After exposure for 6 hours, the growth inhibition rate of Microcystis aeruginosa cells was evaluated by the chlorophyll a content.

[0052] Comparative Example 2

[0053] The cell suspension of Microcystis aeruginosa was exposed to 10 mg / L Cu-MOF, 10 mg / L g-C3N4, 10 mg / L Cu-MOF (dark treatment), and 10 mg / L Cu ions, respectively. After 6 h of exposure, the growth inhibition rate of Microcystis aeruginosa cells was evaluated by measuring the chlorophyll a content.

[0054] Results

[0055] 1. Inhibitory effect on algal cell growth

[0056] The specific results are shown in Table 1. Figure 2 As shown; the results show that the inhibition rate of 10 mg / L Cu-MOF on Microcystis aeruginosa under visible light conditions is significantly enhanced compared with dark conditions, increasing from 8.55% to 31.39%. g-C3N4 has almost no inhibitory effect on the growth of algae. A small amount of g-C3N4 loading (2wt% g-C3N4 / Cu-MOF) does not significantly improve the photocatalytic inactivation efficiency of Cu-MOF. With the increase of g-C3N4 loading, g-C3N4 / Cu-MOF composite nanomaterials show a strong inactivation efficiency on algae cells, among which 10wt% g-C3N4 / Cu-MOF has the best inhibitory effect on algae cell growth, which is 52.13%.

[0057] Table 1 Inhibition and inactivation efficiency of different materials on Microcystis aeruginosa

[0058]

[0059]

[0060] 2. Effect of g-C3N4 loading on the photocatalytic performance of Cu-MOF

[0061] Ultraviolet-visible-diffuse reflectance spectroscopy (UV-vis-DRS) and photoluminescence spectroscopy (PL) were used to characterize g-C3N4, Cu-MOF, 2wt% g-C3N4 / Cu-MOF, 10wt% g-C3N4 / Cu-MOF and 20wt% g-C3N4 / Cu-MOF materials.

[0062] The results are as follows Figure 3 As shown: The loading of g-C3N4 significantly improves the visible light absorption performance of Cu-MOF ( Figure 3 A), the optical band gap value is significantly reduced, and the band gap values ​​of Cu-MOF, 2wt% g-C3N4 / Cu-MOF, 10wt% g-C3N4 / Cu-MOF, and 20wt% g-C3N4 / Cu-MOF are 3.85eV, 3.78eV, 3.55eV, and 3.50eV, respectively. Figure 3 B), but too much g-C3N4 loading will significantly reduce the separation efficiency of electron-hole pairs, limiting the photocatalytic performance of Cu-MOF itself ( Figure 3 C).

[0063] 3. Effect of Cu-MOF nanocomposites with different g-C3N4 loadings on the degradation efficiency of microcystin (MC-LR)

[0064] The MC-LR content was determined by enzyme-linked immunosorbent assay, and the MC-LR standard was purchased from Shanghai Yuanye Biotechnology Co., Ltd. The MC-LR mother solution was added to 10 mg / L Cu-MOF, 2wt% g-C3N4 / Cu-MOF, 10wt% g-C3N4 / Cu-MOF, and 20wt% g-C3N4 / Cu-MOF suspensions to make the final exposure concentration of MC-LR 50 μg / L. After 6 hours of visible light exposure, the Cu-MOF, 2wt% g-C3N4 / Cu-MOF, 10wt% g-C3N4 / Cu-MOF, and 20wt% g-C3N4 / Cu-MOF suspensions were centrifuged (8500 rpm, 30 min) and filtered with a 0.22 μm filter. The MC-LR content was determined at 450 nm using the MC-LR quantitative detection kit (ELISA).

[0065] The results showed that 50 μg / L MC-LR was hardly degraded under 6 h of visible light irradiation, while the concentrations of MC-LR were reduced by 13.0%, 24.3%, 38.1%, and 34.0% respectively when exposed to 10 mg / L suspensions of different materials (e.g. Figure 4 Considering that the light source used is only visible light, the efficiency of 10wt% g-C3N4 / Cu-MOF in photodegrading MC-LR is significantly better than that of Cu-MOF.

[0066] 4. Effect of g-C3N4 loading on the water stability of Cu-MOF

[0067] 20 mg / L g-C3N4, Cu-MOF, 2 wt% g-C3N4 / Cu-MOF, 10 wt% g-C3N4 / Cu-MOF, 20 wt% g-C3N4 / Cu-MOF and 1×10 6 After equal volumes of cells / mL algal cell suspensions were completely mixed, the absorbance at 680 nm was immediately analyzed for 2 h, and the resulting curves were co-settling curves.

[0068] At the same time, the above method was used to measure the single-substance sedimentation curves of 10 mg / L g-C3N4, Cu-MOF, 2wt% g-C3N4 / Cu-MOF, 10wt% g-C3N4 / Cu-MOF, 20wt% g-C3N4 / Cu-MOF nanomaterial suspensions and algae cell suspensions. The single-substance sedimentation curves of each nanomaterial suspension and algae cell suspension were added to obtain the sum-settling curves; the distance between the co-precipitation curve and the sum-settling curve (ΔOD) was used to represent the heterogeneous aggregation effect of nanomaterials and algae cells, proving the water stability of g-C3N4 in Cu-MOF inactivated algae cells.

[0069] The results showed that after 2 h of measurement, g-C3N4 enhanced the heterogeneous aggregation between algae and Cu-MOF, and the ΔOD values ​​of Cu-MOF, 2wt% g-C3N4 / Cu-MOF, 10wt% g-C3N4 / Cu-MOF, and 20wt% g-C3N4 / Cu-MOF increased from 0.05 to 0.08, 0.10, and 0.11 (e.g. Figure 5 As shown), it is demonstrated that the loading of g-C3N4 improves the water stability of Cu-MOF in inactivated algae cells.

Claims

1. A method for inhibiting the growth of Microcystis aeruginosa based on g-C3N4 / Cu-MOF visible light catalytic nanocomposite material, characterized in that: The method comprises exposing the g-C3N4 / Cu-MOF visible light catalytic nanocomposite material to Microcystis aeruginosa; The preparation of the g-C3N4 / Cu-MOF visible light catalytic nanocomposite material includes the following steps: The g-C3N4 powder was dispersed in an organic solvent DMF, and then slowly dropped into a mixed solution of Cu(CH3COO)2·H2O and terephthalic acid, and the mixed solution was vigorously stirred and ultrasonically oscillated; thereafter, it was incubated at 100-120 °C for 6-10 h, and the precipitate was separated after centrifugation, washed, and dried to obtain the obtained product; wherein, the mass proportion of g-C3N4 in the g-C3N4 / Cu-MOF visible light catalytic nanocomposite material was 10wt%.

2. The method according to claim 1, characterized in that The mass ratio of Cu(CH3COO)2·H2O to terephthalic acid is 3.4:

1.

3. The method according to claim 1, characterized in that The centrifugal conditions are 8000-10000 rpm and time 10-20 min.

4. The method according to claim 1, characterized in that: The drying temperature is 40-60°C.

Citation Information

Patent Citations

  • Application of nano copper oxide / carbon nitride composite material in water bloom control

    CN111701613A